2019
DOI: 10.4196/kjpp.2019.23.6.501
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rosmarinic acid on immunoregulatory activity and hepatocellular carcinoma cell apoptosis inH22tumor-bearing mice

Abstract: Rosmarinic acid (RA) is a natural polyphenolic compound that exists in many medicinal species of Boraginaceae and Lamiaceae. The previous studies have revealed that RA had therapeutic effects on hepatocellular carcinoma (HCC) in the H22-xenograft models by inhibiting the inflammatory cytokines and NF-κB p65 pathway in the tumor microenvironment. However, its molecular mechanisms of immunoregulation and pro-apoptotic effect in HCC have not been fully explored. In the present study, RA at 75, 150, and 300 mg/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…However, the authors state that the antioxidative and anti-inflammatory activity of either carnosic acid or carnosol alone is weaker than that of rosemary extract [ 87 ]. Other authors speculate that rosmarinic acid might exhibit an anti-inflammatory activity by inhibition of neutrophil activity, inhibition of MMP-9 activity, and modulation of the NF-κB pathway [ 88 ], accordingly to our findings [ 47 , 48 , 49 , 50 , 51 ].…”
Section: Resultssupporting
confidence: 88%
“…However, the authors state that the antioxidative and anti-inflammatory activity of either carnosic acid or carnosol alone is weaker than that of rosemary extract [ 87 ]. Other authors speculate that rosmarinic acid might exhibit an anti-inflammatory activity by inhibition of neutrophil activity, inhibition of MMP-9 activity, and modulation of the NF-κB pathway [ 88 ], accordingly to our findings [ 47 , 48 , 49 , 50 , 51 ].…”
Section: Resultssupporting
confidence: 88%
“…In recent years, many traditional Chinese medicines, as well as monomeric compounds extracted from certain Chinese medicines, such as phenylpropanoids, flavonoids, saccharides, and alkaloids, have demonstrated outstanding antitumor effects [23]. Researchers have also found that many traditional herbal medicines and molecular compounds derived from herbs show high efficacy in HCC treatment, which can significantly reduce the clinical symptoms and prolong the survival rate of these patients [24]. Our previous studies have confirmed that FZXLG can improve clinical efficacy in patients with HCC after comprehensive minimally invasive treatment as well as liver function and quality of life [25], but high-quality randomized controlled trials are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…RA oral administration to DMBA treated mice repair the expression of p53, Bcl-2, Bax, caspase-3 and 9, indicating that RA may have facilitate or motivate the process of apoptosis during DMBA induced skin carcinogenesis. Cao et al, 2019 (48) attributed chemopreventive mechanism to RA exerts pro-apoptotic effects by inhibiting of STAT3 pathway, thereby upregulating Bax and down-regulating Bcl-2. Nadeem et al, 2019 (49) suggested that, RA's anti-angiogenic effects, as demonstrated through human umbilical vein endothelial cells proliferation, migration, adhesion, and tube formation inhibition.…”
Section: Discussionmentioning
confidence: 99%